The Marble Enterprise - Marinkovich, Zoritsa (Serbia, 2016)
‘The Marble Enterprise’ tells the story of the Communist’s struggle for power in a post-World War II Yugoslavia, where brutally repressive methods affected the lives of more than 500,000 people. Zoritsa Marinkovich depicts the tales of suffering of 16,000 people who endured physical and mental torture for allegedly opposing national politics.
Verzio Film Festival Submission
Keywords: Documentary films